Influence of an oxidation of the carbon fiber surface by boiling nitric acid on the adhesion strength in carbon fiber‐acrylate composites cured by electron beam. (13th August 2012) - Vautard, F.; Fioux, P.; Vidal, L.; Dentzer, J.; Schultz, J.; Nardin, M.; Defoort, B.
<x xml:space="preserve">Abstract</x> A time‐dependent oxidation of carbon fibers in boiling nitric acid was used to investigate the influence of a modification of the fiber surface properties on the adhesion strength with an acrylate resin cured by electron beam (EB). For each time of treatment, a characterization of the surface topography and the surface chemistry was done (topography at a micrometric and nanometric scale, specific surface area, temperature programmed desorption, X‐ray photoelectron spectroscopy analysis). The oxidation of the fiber surface in boiling nitric acid created a rough surface, which significantly increased the specific surface area, and also generated a high density of hydroxyl groups, carboxylic acids and lactones in comparison to untreated fibers. The adhesion strength with the acrylate resin cured by EB was measured by a pull‐out test. For comparison, an isothermal ultraviolet curing of the matrix was also investigated. The value of the interfacial shear strength, determined by the Greszczuk's model, was increased by the oxidation of the carbon fiber surface for both curing processes, but lower values were systemically obtained with EB curing. Copyright © 2012 John Wiley & Sons, Ltd.